PENGEMBANGAN MEDIA FLIPBOOK BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN MINAT DAN LITERASI PADA MUATAN SENI MUSIK SISWA KELAS V SEKOLAH DASAR - Noor Aini, Alfina; Eka Titi Andaryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a local wisdom-based flipbook medium in music education to enhance the interest and literacy of fifth-grade elementary school students. The research method employed was the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results showed that the developed flipbook successfully increased students' interest and literacy significantly. Pretest data indicated that the average interest score was 58.2, and the literacy score was 60.5. After implementing the flipbook medium, posttest results showed an increase, with the average interest score reaching 78.6 and the literacy score rising to 82.4. The instruments used in this study were tested for validity and reliability, showing that all items were valid and had high reliability (Cronbach's Alpha = 0.89 for interest and 0.87 for literacy). These findings indicate that the local wisdom-based flipbook is effective in enhancing students' interest and literacy in music education. Keywords: Flipbook, Local Wisdom, Interest, Literacy, Music Education